Lessons from the Case History of a Massive Landslide Dam - Fawad S. Niazi; Aranzazu Pinan-Llamas; Kamran Akhtar (Geofluids)
A massive landslide created a natural dam on two tributaries of Jhelum River near the town of Hattian Bala in Kashmir in October 2005. The landslide was triggered by a 7.6 Mw earthquake. The resulting unconsolidated dam and water impoundment upstream carried hazard potential of downstream damage to both infrastructure and population due to potential flooding caused by its breach. Comprehensive investigations and monitoring were implemented to analyse dam stability. Fresh topographic profiles were generated. Samples of the matrix materials were utilized in the laboratory investigations including grain-size analysis, laboratory electrical resistivity and permeability tests at varying densities and degrees of saturation, and sediment concentration assessment in the seepage discharge. A noninvasive geophysical method was employed together with new topographic information to develop transient subsurface pictures and to assess the advancement of seepage fronts within the dam body. Internal erosion/filtering potential of the matrix material was assessed by comparing grain size distributions with those of the earlier failed dams. Upstream inflows, downstream discharges, daily precipitation, and lake levels monitored during the study period were utilized in hydrological data analysis in an attempt to assess the potential seepage volume. A combination of empirical, analytical, and numerical methods and simulations, together with laboratory and field investigations, led to the interpretations regarding short- and long-term stability of the dam. This paper highlights alternative methods of investigation employed differently from those used by other national and international agencies in analysing the failure potential of this natural dam. It offers lessons learned from a case history that can be beneficial in future evaluation of seepage-induced failure of similar natural features.